Treatment of choledochal lithiasis - Salom, Andrés; Estapé Viana, Gonzalo; Acevedo, Carlos; Harguindeguy, Martín; Ettlin, Alejandro; Alvez, Martín; Touya, Guillermo; Baldi, Daniel; Peyroulou, Alfredo (Cirugía del Uruguay, 2004)
This paper presents the results achieved with patients treated for lithiasis of common bife duct within the /ast five years, at the Central Hospital of the Armed Forces. Case material invo/ves 100 cases, 77 of which were operated through laparotomy and 23 through laparoscopíc surgery Wíthín the group of those operated by laparotomy, 40 were treated through a choledochotomy, a choledocho-/ítotomy and draínage through a Kehr tube; in 18 cases ca/cutí were extracted through the trans-cystíc path. Fífteen choledochoduodenostomíes, 1 hepatojejunostomy, 2 transduodenal surgícal papillotomíes were performed and 1 patíent underwent left liver resection. Within the group of those treated through laparoscopíc surgery, 15 cases were resolved through the transcystíc path and 2 through cho/edochotomy Six conversíons were performed and there were 2 complícatíons (a bílioma and a residual líthiasis). Twenty-cases of CPER wíth papíl/otomy, were performed whether independently or combined with surgery.